Creating and Interpreting Visual Storytelling Art in Extending Thematic Apperception Tests and Jung's Method of Interpreting Dreams - Woodside, Arch; Sood, Suresh; Muniz, Karlan (Emerald Group Publishing Limited, 2013)
The main thesis here is that the stories that some brands tell to consumers enable consumers to achieve archetypal experiences. Examining the stories consumers tell in natural contexts involving shopping for and using brands informs explanations of associations of archetypes, brands, and consumers. The study advances the use of degrees-of-freedom analysis (DFA) and creating visual narrative art (VNA) as useful steps for confirming or disconfirming whether or not the stories consumers tell have themes, events, and outcomes that match with the core storylines told by brands. As a proposal, an extension of thematic apperception tests (TATs) is relevant in applying the DFA to brand-consumer storytelling research. The study includes a review of early work on TATs, DFA, archetypal theory, and how brands become icons. The study’s theory, method, and findings provide useful tools for brand managers and researchers on issues that relate to psychology and marketing.